2017
DOI: 10.1038/cr.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

IPA1 functions as a downstream transcription factor repressed by D53 in strigolactone signaling in rice

Abstract: Strigolactones (SLs), a group of carotenoid derived terpenoid lactones, are root-to-shoot phytohormones suppressing shoot branching by inhibiting the outgrowth of axillary buds. DWARF 53 (D53), the key repressor of the SL signaling pathway, is speculated to regulate the downstream transcriptional network of the SL response. However, no downstream transcription factor targeted by D53 has yet been reported. Here we report that Ideal Plant Architecture 1 (IPA1), a key regulator of the plant architecture in rice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(198 citation statements)
references
References 75 publications
2
189
0
Order By: Relevance
“…Consequently, we demonstrated that dormant genes, including DRM1 to DRM4 and OsNCED1 , were upregulated in the leaf primordia rather than in the meristem of the axillary bud. Recently, it was reported that SLs work at least partly through OsSPL14 to suppress bud outgrowth in rice (Song et al ., ). We showed that OsSPL14 mRNA exclusively accumulates in the leaf primordia and is excluded from the axillary meristem as well as the SAM (Luo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Consequently, we demonstrated that dormant genes, including DRM1 to DRM4 and OsNCED1 , were upregulated in the leaf primordia rather than in the meristem of the axillary bud. Recently, it was reported that SLs work at least partly through OsSPL14 to suppress bud outgrowth in rice (Song et al ., ). We showed that OsSPL14 mRNA exclusively accumulates in the leaf primordia and is excluded from the axillary meristem as well as the SAM (Luo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulation of PIN protein on the plasma membrane is enhanced in the absence of SL, allowing establishment of auxin flow between the axillary bud and the main stem (Crawford et al, 2010;Shinohara et al, 2013). In the second proposed mode of SL action, SL works through the control of downstream transcription cascades (Braun et al, 2012;Brewer et al, 2015;Liu et al, 2017;Song et al, 2017). In rice and wheat, SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) genes, encoding plant-specific transcription factors, were identified as D53 targets that suppress bud outgrowth (Liu et al, 2017;Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly formed protein complex polyubiquitinates transcriptional repressors D53/SMXL6/7/8, thereby triggering 26S proteasomeā€mediated degradation of D53/SMXL6/7/8 that allows the expression of SLā€responsive genes for various physiological functions (Figure b; Waters et al, ; Yao et al, ). For instance, it has recently been reported in rice that IDEAL PLANT ARCHITECTURE1, a SQUAMOSA PROMOTER BINDING PROTEINā€LIKE transcription factor, acts as a direct downstream target of D53 in regulating tiller development and SLā€mediated gene expression (Song et al, ).…”
Section: Sl Biosynthesis and Signal Transduction In Plantsmentioning
confidence: 99%
“…In addition, DLT controls rice tillering and plant height through influencing the BR signaling pathway (Tong et al ). D53 interacts with IPA1, influencing IPA1 transcriptional activity and tillering (Song et al ), whereas IPI1 controls the tissueā€specific degradation of IPA1 and hence, regulates tillering and the number of primary and secondary rachis branches (Wang et al ).…”
Section: The Major Cloned Genes Related To Source Sink and Flowmentioning
confidence: 99%